2016
DOI: 10.1158/2159-8290.cd-16-0008
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A Haploinsufficiency Transforms FLT3ITD Myeloproliferative Disease into a Rapid, Spontaneous, and Fully Penetrant Acute Myeloid Leukemia

Abstract: Cytogenetically normal acute myeloid leukemia (CN-AML) represents nearly 50% of human AML. Co-occurring mutations in the de novo DNA methyltransferase DNMT3A and the FMS related tyrosine kinase 3 FLT3 are common in CN-AML and confer a poorer prognosis. We demonstrate that mice with Flt3-internal-tandem duplication (Flt3ITD) and inducible deletion of Dnmt3a spontaneously develop a rapidly-lethal, completely-penetrant, and transplantable AML of normal karyotype. AML cells retain a single Dnmt3a floxed allele, re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 75 publications
0
68
0
Order By: Relevance
“…The contribution of these Dnmt3a-null HSCs to blood production is minimal, reflecting an imbalance between self-renewal and differentiation driven by loss of DNMT3A (bottom). myeloid cancers (Meyer et al 2016;Yang et al 2016). Taken together, these data strongly indicate that DNMT3A is a haploinsufficient tumor suppressor gene in myeloid leukemias, when cooperating mutations are present.…”
Section: Dnmt3a Mutations and Cancermentioning
confidence: 58%
See 2 more Smart Citations
“…The contribution of these Dnmt3a-null HSCs to blood production is minimal, reflecting an imbalance between self-renewal and differentiation driven by loss of DNMT3A (bottom). myeloid cancers (Meyer et al 2016;Yang et al 2016). Taken together, these data strongly indicate that DNMT3A is a haploinsufficient tumor suppressor gene in myeloid leukemias, when cooperating mutations are present.…”
Section: Dnmt3a Mutations and Cancermentioning
confidence: 58%
“…The mutant protein can dimerize with WT DNMT3A, but tetramers, which comprise a substantially more active form of the protein, are not able to form (Holz-Schietinger et al 2012;Russler-Germain et al 2014). The resulting low levels of DNMT3A homotetramers result in a significant reduction of methytransferase activity, providing an explanation for the genome-wide hypomethylation observed in patients with R882 mutations (Cancer Genome Atlas Research 2013;Qu et al 2014;Meyer et al 2016;Yang et al 2016). In addition, the R882 mutant may acquire other deleterious interactions.…”
Section: Dnmt3a Mutations and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…116 A recent study showed that the rescue of DNMT3a expression is accompanied by DNA re-methylation in an AML murine model, indicating that the oncogenic effects of mutant DNMT3a are reversible. 117 Over the past decade, it has become clear that miRNAs can be inactivated by epigenetic mechanisms, such as DNA hypermethylation of CpG sites within CpG islands. Kaiso, which binds to methyl-CpG dinucleotides, could inhibit the expression of miR-31 and promote prostate cancer metastasis.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…These classes of mutations exhibit complex genetic interactions with each other, some showing high propensity of co-occurrence and some showing mutual exclusivity (Chen et al, 2013). Efforts to model the complex mutational landscapes of human AML in animal models have relied largely on mouse genetics by crossing few mutant strains or by introducing the mutant allele by gene transfer, which requires large time- and resource-commitments (Guryanova et al, 2016; Meyer et al, 2016; Shih et al, 2015; Yang et al, 2016). New methods to systematically generate multiple AML animal models with complex mutational landscapes should accelerate the discovery of vulnerabilities shared among AMLs with different genotypes and those that are genotype specific.…”
Section: Introductionmentioning
confidence: 99%